Use of thrombopoietin receptor agonists in adults with immune thrombocytopenia: a systematic review and Central European expert consensus - Pulanić, Dražen; Bátorová, Angelika; Bodó, Imre; Červinek, Libor; Ionita, Ioana; Lissitchkov, Toshko; Melikyan, Anahit; Podolak-Dawidziak, Maria (Annals of hematology, 2023)
There are currently three thrombopoietin receptor agonists (TPO-RAs) approved in Europe for treating patients with immune thrombocytopenia (ITP): romiplostim (Nplate®), eltrombopag (Revolade®), and avatrombopag (Doptelet®). However, comparative clinical data between these TPO-RAs are limited. Therefore, the purpose of this study was to perform a literature review and seek expert opinion on the relevance and strength of the evidence concerning the use of TPO-RAs in adults with ITP. A systematic search was conducted in PubMed and Embase within the last 10 years and until June 20, 2022. A total of 478 unique articles were retrieved and reviewed for relevance. The expert consensus panel comprised ITP senior hematologists from eight countries across Central Europe. The modified Delphi method, consisting of two survey rounds, a teleconference and email correspondence, was used to reach consensus. Forty articles met the relevancy criteria and are included as supporting evidence, including five meta-analyses analyzing all three European-licensed TPO-RAs and comprising a total of 31 unique randomized controlled trials (RCTs). Consensus was reached on seven statements for the second-line use of TPO-RAs in the management of adult ITP patients. In addition, the expert panel discussed TPO-RA treatment in chronic ITP patients with mild/moderate COVID-19 and ITP patients in the first-line setting but failed to reach consensus. This work will facilitate informed decision-making for healthcare providers treating adult ITP patients with TPO-RAs. However, further studies are needed on the use of TPO-RAs in the first-line setting and specific patient populations.
Keywords: idiopatická trombocytopenická purpura; receptory Fc; Thrombocytopenia; Thrombopoietin; Consensus; Receptors, Fc; Immune thrombocytopenia; Receptors, Thrombopoietin; receptory thrombopoetinu; konsensus; Eltrombopag; Purpura, Thrombocytopenic, Idiopathic; COVID-19; Systematic review; Thrombopoietin receptor agonists; Adult; Romiplostim; Avatrombopag; Humans; Recombinant Fusion Proteins; rekombinantní fúzní proteiny; trombocytopenie; thrombopoetin; Benzoates; Hydrazines; dospělí; hydraziny; benzoáty; lidé